Study of the reverse delta wing - Altaf, Afaq; Omar, Ashraf Ali E.; Asrar, Waqar (American Institute of Aeronautical and Astronautic, 2011)
Particle image velocimetry was used in a low-speed wind tunnel to investigate the vortex structures of a slender reverse delta wing at various angles of attack and roll. This work investigates the characteristics of the vortices generated downstream in planes perpendicular to the freestream direction and their dependence on angles of attack and roll at a chord-based Reynolds number of Rec= 382000 The peak tangential velocities atangle of attack higher than 5 deg show a trend similar to a delta wing. A six-component balance was used to obtain the aerodynamic coefficients for a reverse delta wing as well as a delta wing for comparison. A simulation of the streamlines, velocity vectors, and surface pressure contours was carried out using computational fluid dynamics software to show the characteristics of the flow over a reverse delta wing.